Pre-Primary Education Provision in Zanzibar: : Educational Stakeholders Perceptions on the Provision of Pre-Primary Education - Ali Chai Ali; Ignasia Renatus Mligo; Florentina Shaghembe Nsolezi (International Journal of Educational Administration, Management, and Leadership, 2022)
Early childhood education is a critical period of rapid, cognitive and psychosocial development of a child. The quality of education received by a child at this important age determines to a large extent the level of his or her physical, cognitive and social development. In Zanzibar, pre-primary school education (PPE) is an aspect of two years compulsory basic education provided to children attained four to five years of age. The intention is to increase the access of children to basic education in the Islands. This paper explores educational stakeholder’s perceptions on the provision of PPE in Zanzibar. The study employed qualitative methodology and a case study design where only PPE level among other levels of education was involved. A total number of 22 participants participated in the study where by 07 were pre-primary school teachers, 04 were pre-primary school head teachers, 05 were quality assurance officer from the Ministry of Education and 06 were parents. Data was generated by using focus group discussion, semi structured interviews as well as documentary review. The results of the study revealed varied educational stakeholders perceptions on pre-primary education which influenced by educational qualification of the participants, awareness, involvement, cost incurred, experience and expectations in PPE. The study concludes that success in PPE is a result of parental involvement and partnership with teachers. That is to argue that interactions between parents and teachers as well the introduction of teaching/learning resources and facilities in PPE schools are unavoidable for better provision of PPE.